The Effectiveness of Using Newspaper in Reading Comprehension At Tenth Grade Student of SMAN 6 Muaro Jambi - Yanti Ismiyati; Ridho Praja Dinata (Universitas Batanghari Jambi, 2021)
The objectives of the research are to how the effectiveness of using newspaper article to teach reading comprehension. Moreover, this research designed to study how the newspaper article can be implemented in the tenth grade students of SMA N 6 Muaro Jambi. The method used in this research is quantitative research design. The subject of the research is the ten grade students of SMA N 6 Muaro Jambi. There are 30 students of the ten class X MIA 1 and 30 students of the ten class X MIA 2. The result showed there is a significant effect on the students’ reading comprehension between those who were taught by using newspaper article and those who were taught without newspaper article. In this research, the null hypothesis is rejected because the value of t-test is higher than the value of t-table (1.93 > 1.47). Then, the alternative hypothesis is accepted, the value of t-test is higher than the value of t-table (1.93 > 1.47). Thus, it proved that there is the effect of using think pair share technique to develop students’ reading skills on tenth grade students’ of SMA N 6 Muaro Jambi Jambi. In conclusion, it was found that there is improvement score on the students who were taught by newspaper article. This can be seen from pre-test result, treatment and post test result after treatment. Teaching English learning by using newspaper article in experimental class was effective.